Strategic latency with temporal mutualism: a coevolutionary model of the host–varicella-zoster virus relationship - Han, Dong-Gyun (Frontiers in Immunology, 2025)
After primary infection with varicella, varicella-zoster virus (VZV) establishes a latent state that precedes the clinical manifestation of herpes zoster. Growing evidence, however, indicates that latency is not merely quiescent but represents an active immunological adaptation. We propose the immunosensor hypothesis, in which VZV latency within sensory ganglia contributes to host immune surveillance while simultaneously ensuring viral persistence. Using a game-theoretical framework, we conceptualize this interaction as a temporally partitioned evolutionarily stable strategy (TP-ESS). In this model, VZV progresses through three sequential phases across the host lifespan: (i) aggressive replication and transmission during primary infection, (ii) immunomodulatory latency during immune competence, and (iii) reactivation during immune decline. Each phase represents a dynamic equilibrium shaped by host immunity and viral life-history trade-offs. The TP-ESS framework integrates viral ecology, innate immunity, and neurovirology into a unified model of latency and reactivation, providing a conceptual basis for epidemiological patterns of herpes zoster and generating testable predictions on immunity-dependent viral behavior and host–virus coadaptation.